Murabahah Contract in Islamic Trade Finance Instruments in Malaysia - Abdul Rahim, Ahmad Khilmy; Ahmad Razimi, Mohd Shahril; Mohd Noor, Mohd Murshidi (2016)
Islamic Trade Finance (ITF) instruments were introduced in Islamic banking system in Malaysia since the early 1990s when there is a need for Islamic instruments in commerce especially in international trade. In order to be accepted in Islamic Finance transactions, some amendments have been made so that it will be „shariah compliant? by applying muamalat contracts in those products. There are several muamalat Contracts applied in ITF instruments namely murabahah, wakalah, bay’ al-dayn, kafalah, tawarruq and wadi’ah. The most commonly used contract is murabahah which is applied in Letter of Credit (LC), Working Capital Financing (WC), Trust Receipt (TR) and Accepted Bills. This article analyses the application of murabahah contract in Islamic Trade Finance (ITF) instruments namely Letter of Credit (LC-i), Working Capital (WC-i), Trust Receipt (TR-i) and Accepted Bills (AB-i). This article concludes that there are several Shari?ah issues related to the application of murabahah in the facilities mentioned such as al-muwaadah, ownership and prising of the subject matter (al-ma’qud alaih)